Customer's satisfaction and service quality towards frontline staff at Yayasan Sarawak / Nur Affiqah Alwi - Alwi, Nur Affiqah (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
The study was a descriptive research to investigate the elements that can identify the customers'satisfaction and service quality towards frontline staff at Yayasan Sarawak. The entire report of the study was structured into five (5) chapters. Chapter one was a presentation of the background of the study, problem statement, objectives, research questions, significance and scope of the study. The majority of respondents are female respondents. The highest respondents are from the 20 years old and below. The single respondents are the majority of marital status and Chinese is the most race group of the respondent. The occupational is most for the respondents that are from private sector. Chapter two was a comprehensive presentation of the literature that was reviewed for the study. These were relevant concepts and theories of the research topic. They include the concepts of customer satisfaction, front line staff and service quality. Chapter Three was the methodology of the study, it presented the research design, population, sampling technique,sample size, unit of analysis, instrument, data collection procedure and data analysis. Chapter Four was a presentation and analysis of the data collected. It started with a profile of the respondents (customers) and descriptive statistics of service quality and customer satisfaction.